CODE MIXING ANALYSIS ON TIMELESS BEGINS ALBUM BY CROSS GENE: ANALISIS CAMPUR KODE PADA ALBUM TIMELESS BEGINS OLEH CROSS GENE - Gifted Gifted; Diana Kartika (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
This research is entitled "Code Mixing Analysis on the Album Timeless Begins by Cross Gene". The author's background in conducting this research is because communication at this time is not only communication with one language but is interested in two or more languages. Society nowadays communicates bilingual so that researchers feel interested in researching two different languages  used by the general public.  So this study aims to determine the form of code mixing in the lyrics of the album Timeless Begins by Cross Gene. The results of the research shows that from 126 data had been processed,it was found 31 words form, 60 phrase forms, 1 baster form, 3 reduplication form , 30 clause form. The code in this study  in the form of factors from the popular term, namely 4, only prestigious factor 2, code imitation factor 2, topic factor 1, variety and speech level factor 1, personal factor speaker 1, and function and objective factor 1.